Green sanctuaries: residential green and garden space and the natural environment mitigate mental disorders risk of diabetic patients - Erxu Xue; Jianhui Zhao; Jingyu Ye; Jingjie Wu; Dandan Chen; Jing Shao; Xue Li; Zhihong Ye (BMC Medicine)
Abstract Background The co-occurrence of diabetes and mental disorders is an exceedingly common comorbidity with poor prognosis. We aim to investigate the impact of green space, garden space, and the natural environment on the risk of mental disorders among the population living with diabetes. Methods We performed a longitudinal analysis based on 39,397 participants with diabetes from the UK Biobank. Residential green and garden space modeled from land use data and the natural environment from Land Cover Map were assigned to the residential address for each participant. Cox proportional hazards model was used to analyze the associations between nature exposures and mental disorders of diabetes. Casual mediation analysis was used to quantify indirect effect of air pollution. Results During a mean follow-up of 7.55 years, 4513 incident mental disorders cases were identified, including 2952 depressive disorders and 1209 anxiety disorders. Participants with natural environment at 300 m buffer in the second and third tertiles had 7% (HR = 0.93, 95%CI: 0.86–0.99) and 12% (HR = 0.88, 95%CI: 0.82–0.94) lower risks of incident mental disorders compared with those in the first tertile, respectively. The risk of mental disorders incidence among diabetes patients will decrease by 13% when exposed to the third tertile of garden space at 300 m buffer. The natural environment and garden space individually prevented 6.65% and 10.18% of mental disorders incidents among diabetes patients. The risk of incident mental disorders was statistically decreased when exposed to the third tertile of green space at 1000 m buffer (HR = 0.84, 95% CI: 0.78–0.90). Protective effects of three nature exposures against depressive and anxiety disorders in diabetes patients were also observed. Air pollution, particularly nitrogen dioxide, nitrogen oxides, and fine particulate matter, significantly contributed to the associations between nature exposures and mental disorders, mediating 48.3%, 29.2%, and 62.4% of the associations, respectively. Conclusions Residential green and garden space and the natural environment could mitigate mental disorders risk in diabetes patients, with air pollution playing a vital mediator. This highlights the potential for local governments to enhance the sustainability of such interventions, grounded in public health and urban planning, through strategic planning initiatives. Graphical Abstract